Controllable AgNPs encapsulation to construct biocompatible and antibacterial titanium implant - Wei, Zhangao; Li, Kexin; Wang, Shuang; Wen, Lan; Xu, Linghan; Wang, Yankai; Chen, Zirui; Li, Wei; Qiu, Hua; Li, Xiangyang; Chen, Jialong (Frontiers in Bioengineering and Biotechnology, 2022)
Silver nanoparticles (AgNPs) are progressively becoming an in-demand material for both medical and life use due to their effective antimicrobial properties. The high surface area-to-volume ratio endows AgNPs with enhanced antibacterial capacity accompanied by inevitable cytotoxicity. Surface coating technique could precisely regulate the particle shape, aggregation, and Ag+ release pattern of AgNPs, by which the cytotoxicity could be significantly reduced. Various coating methods have been explored to shell AgNPs, but it remains a great challenge to precisely control the aggregation state of AgNPs and their shell thickness. Herein, we proposed a simple method to prepare a tunable polydopamine (pDA) coating shell on AgNPs just by tuning the reaction pH and temperature, yet we obtained high antibacterial property and excellent biocompatibility. SEM and TEM revealed that pDA coated AgNPs can form core-shell structures with different aggregation states and shell thickness. Both in vitro and in vivo antibacterial tests show that acid condition and heat-treatment lead to appropriate AgNPs cores and pDA shell structures, which endow Ti with sustained antibacterial properties and preferable cell compatibility. One month of implantation in an infected animal model demonstrated that the obtained surface could promote osteogenesis and inhibit inflammation due to its strong antibacterial properties. Therefore, this study provides a promising approach to fabricate biocompatible antibacterial surface.